2020
DOI: 10.1055/s-0040-1709182
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Arthroscopic Arthrolysis in the Treatment of Arthrofibrosis: A Systematic Review

Abstract: Stiffness after total knee arthroplasty (TKA) remains a clinical challenge for health care professionals. Historically, arthroscopic arthrolysis is a treatment modality that has been reserved for patients that have failed other conservative modalities, including manipulation under anesthesia. However, a systematic review of the literature evaluating the clinical efficacy and complications of arthroscopic arthrolysis for stiffness after TKA has not been performed. A systematic review of medical databases (PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Compared with open surgery, arthroscopic arthrolysis has the advantages of less tissue trauma, less postoperative pain, fewer complications, faster recovery and better outcome. However, arthroscopic arthrolysis is insufficient to treat knee arthrofibrosis caused by a combination of extra-articular factors, which may require additional open surgery technique such as quadricepsplasty [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with open surgery, arthroscopic arthrolysis has the advantages of less tissue trauma, less postoperative pain, fewer complications, faster recovery and better outcome. However, arthroscopic arthrolysis is insufficient to treat knee arthrofibrosis caused by a combination of extra-articular factors, which may require additional open surgery technique such as quadricepsplasty [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arthrofibrosis after TKA remains a challenging complication, with poor non-surgical and surgical treatment options. 7 , 26 Arthrofibrosis also complicates other orthopaedic conditions and procedures. For persistently stiff joints, arthroscopic or open lysis of adhesions may be indicated, although with serious limitations, as scar tissue often reaccumulates, again restricting motion.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are comparable with findings of a recent systematic review examining arthroscopic LOA and MUA for postoperative knee arthrofibrosis in TKA patients. 3 Patients in the review by Cohen et al 3 had a mean preoperative arc of motion of 60.8° that improved 32.5° after LOA to a final mean arc of motion of 93.3°. Our study demonstrated a similar improvement, as patients started with a mean arc of motion of 81.1° that improved 41.6° after LOA to a final mean arc of motion of 122.6°.…”
Section: Discussionmentioning
confidence: 99%